2014
DOI: 10.19159/tutad.09721
|View full text |Cite
|
Sign up to set email alerts
|

Yalova İlindeki Süt Sığırcılığı İşletmelerinin Yapısal Özelliklerini Etkileyen Faktörler: Yem ve Besleme Alışkanlıkları

Abstract: Özet: Bu araştırma Yalova ilindeki süt sığırcılığı işletmelerinin yem ve besleme alışkanlıklarına hayvan sayısı ve yetiştiricilerin eğitim seviyesinin etkilerini belirlemek amacı ile yapılmıştır. Araştırmanın materyalini il genelinden şansa bağlı olarak belirlenen 324 adet süt sığırı işletmesinde yapılan anket yoluyla elde edilen veriler oluşturmaktadır. Veriler SPSS 20.0 paket programında crostabb analizi edilerek ki kare testi yapılmıştır. İşletmelerde en çok kullanılan kaba yem kombinasyonu çayırotu+saman o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
1
2
2
1
Order By: Relevance
“…Similarly, percentages of cattle farms produced their own forage crops in Kars Province, in Muş Province, Narman county, in Tekirdağ and Kırklareli provinces were reported as 87.8%, 80.8%, 88.7%, 91.6% and 81.8% respectively by Demir et al, (2013), Bakır and Kibar, (2018), Diler et al, (2018) and Öztürk et al, (2019). On the contrary of results of the present study, findings of other studies conducted in Turkey revealed lower percentages of enterprises produced their own forage crops in Konya (47.2%) as well as and in Ergani (9.0%), in Yalova (61.2%), in Erzurum (16%) (Uzal and Uğurlu 2006;Bakır and Han 2009;Demir andHan, 2014 andDiler et al 2016). It was also determined that there was a significant (P<0.01) relationship between forage crop production and the size of the enterprises.…”
Section: Forage Crop Productioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Similarly, percentages of cattle farms produced their own forage crops in Kars Province, in Muş Province, Narman county, in Tekirdağ and Kırklareli provinces were reported as 87.8%, 80.8%, 88.7%, 91.6% and 81.8% respectively by Demir et al, (2013), Bakır and Kibar, (2018), Diler et al, (2018) and Öztürk et al, (2019). On the contrary of results of the present study, findings of other studies conducted in Turkey revealed lower percentages of enterprises produced their own forage crops in Konya (47.2%) as well as and in Ergani (9.0%), in Yalova (61.2%), in Erzurum (16%) (Uzal and Uğurlu 2006;Bakır and Han 2009;Demir andHan, 2014 andDiler et al 2016). It was also determined that there was a significant (P<0.01) relationship between forage crop production and the size of the enterprises.…”
Section: Forage Crop Productioncontrasting
confidence: 99%
“…Percentage of utilization from silage was already reported at a similar level by Diler et al (2018). In the other similar studies, Diler et al ( 2016) revealed extremely low level of silage usage (0.25%), while Kurt et al (2020), Aydın and Keskin (2019), Özyürek et al (2014), Bakır and Han (2014), Özdemir and Karaman (2008) and Önal and Özder (2008) reported the percentages of the silage using enterprises as 18.8%, 30.0%, 13.0%, 21.4%, 30.0%, and 96.5% respectively. Silage supply in the enterprises was mostly made by purchasing (73.7%).…”
Section: Sources Of Roughage and Concentrate Feed Supplymentioning
confidence: 71%
“…In addition, 7.6% of the cattle breeders bought the concentrate feed from feed mills whenever their needs were not met by their production, and 2.8% of those provided it from Agricultural Credit Cooperatives. The result is in accordance with Figure 5: Percentages of enterprises that grow fodder crops according to the number of animals Şekil 5: Hayvan sayılarına göre yem bitkileri yetiştiren işletmelerin yüzde oranları findings of Bakır and Han (2014) who studied the structural features of dairy cattle breeding enterprises in Yalova province. They reported that 87.1% of enterprises purchased concentrate feeds from feed dealers, while 10.9% and 1.9 % from unions and cooperatives as well as feed mills respectively.…”
Section: Sources Of Roughage and Concentrate Feed Supplysupporting
confidence: 84%
“…Similarly, more than 3/4 of the cattle enterprises in Antalya, Iğdır, Kars, Muş, Tekirdağ, Kırklareli provinces as well as Narman county of Erzurum province grew fodder crops, that they needed, on their own farms (Kum, 2006;Yeşil, 2015;Demir et al, 2013;Bakır and Kibar, 2019;Öztürk et al, 2019;Diler et al, 2018). On the contrary of results of the present study, findings of other studies carried out in different regions of Turkey revealed lower percentages (47.2% in Konya 52.0 in Tekirdağ, 61.2% in Yalova, 16% in Hınıs county of Erzurum province) of enterprises which grew their own forage crops (Uzal and Uğurlu 2006;Soyak et al 2007;Bakır and Han, 2014;Diler et al 2016).…”
Section: Sources Of Roughage and Concentrate Feed Supplycontrasting
confidence: 79%
See 1 more Smart Citation